SOCIODRAMA METHOD WITH STUDENTS' PRAISEABLE MORALS STATE ELEMENTARY SD NEGERI 040470 LINGGA JULU, KEC.SIMPANG EMPAT - Ade Ridho Rejeki (Journal of Educational Science Learning and Research, 2024)
The learning methods commonly used by most teachers are discussion, lecture and question and answer methods, where the teacher is the center of information, so that students become less active and only as recipients of information. The sociodrama method is to dramatize behavior in relation to social problems. The sociodrama method used is expected to carve out commendable morals in oneself through habituation in daily life. The commendable morals formed through the sociodrama method are expected to be morals towards Allah, morals towards humans, and morals towards parents. The purpose of this study specifically is to determine the relationship between the sociodrama method and students' commendable morals. This study was conducted in Class VI of Elementary School 040470 Lingga Julu, Simpang Empat District. The data collection technique was a questionnaire distributed to 23 respondents who were students of Elementary School 040470 Lingga Julu, Simpang Empat District. The results of the study on the relationship between the sociodrama method and students' commendable morals can be seen from the Pearson moment correlation analysis obtained a significance value of less than 0.05, namely 0.023 <0.05, so the research hypothesis is accepted. This means that there is a relationship between the sociodrama method and the commendable morals of students at Elementary School 040470 Lingga Julu. The conclusion of this study is that there is a fairly strong relationship between the sociodrama method and the commendable morals of students at Elementary School 040470 Lingga Julu, Simpang Empat